Change, Choice and Inference: A Study of Belief and Revision and Nonmonotonic Reasoning. - Wheeler, Gregory (Philosophy of Science, 2005)
The article reviews the book "Change, Choice and Inference: A Study of Belief and Revision and Nonmonotonic Reasoning," by Hans Rott.